PENGEMBANGAN SISTEM DISPLAY INFORMASI UNTUK DESA SUKAPURA - Suakanto, Sinung; Ambarsari, Nia; Kusumasari, Tien Fabrianti; Fahrizky, Bimo Agung (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Current information is a need that needs to be conveyed by certain parties to the audience. Community services also need to convey information so that it can be well received by the community. This is what is currently also needed by Sukapura Village, especially the Village Hall in providing information to the community. The Village Office wants to equip the Village Hall office with equipment that can provide information to the public or visitors to the Village Hall. To help with this, community service activities need to be carried out. This community service activity will be carried out to develop a display information system that is placed outdoors so that it is easily read by visitors or the public who pass through it. The need for this information will be a support for services at the Sukapura village hall. The tool used uses an LED-based Running Text device. To change the information in it, you can use application assistance from both Android applications and using laptop / computer-based applications. With this system, it is hoped that the community can easily obtain information, not only general information, but other information related to Sukapura Village.